Signs binding at indoor pools as a system supporting the safety and hygiene of water recreational and sport activity - Łubkowska, Wioletta; Szark-Eckardt, Mirosława; Żukowska, Hanna (Quality in Sport, 2015)
The aim of the research was to determine the level and nature of risks occurring in the sign zone of indoor pools relating to required safety rules. The research was conducted at 29 facilities located in ten provinces. The method of qualitative field research was applied. It was found that at more than half of the examined indoor pools (51.7%) the A-8 prohibitory sign “jumping into water is prohibited” had the graphic form that was inconsistent with the binding provisions. The information signs: C-2 – “dangerous depth of water” and C-3 – “sudden drop” occurred only at 27.6% of examined facilities. Within the scope of non-legal signs – communicators it was found that there is no uniform manner of providing information. The symbols used is very diverse which causes chaos in the form of various markings. In order to improve the safety of persons using the indoor pools, activities aiming at developing and introducing uniform models of markings should be undertaken, which constitutes a necessary condition of full participation in modern physical culture.